Visual-based Acculturation in Balinese Wayang for the Characters of Jesus and Mary - Andreas James Darmawan; Martinus Dwi Marianto; I Ketut Suteja (ITB Journal Publisher, DRPM ITB, 2025)
Beauty plays a vital role in persuasive communication, encompassing values such as goodness, usefulness, splendor, comfort, novelty, and metaphorical strength. This study aimed to reinterpret figures of Jesus and Mary through visual language of Balinese wayang, integrating traditional Balinese cultural values. Western visual portrayals often dominate depictions of these Biblical figures, making them appear generic and less engaging to contemporary audiences. Using a qualitative method, with Bishop Robert Barron’s research synthesis of Aristotle, Aquinas, and Balthasar aesthetic, which emphasizes evangelization through beauty. The concept of beauty is explored and expanded toward goodness and truth. Visual designs were developed through literature on Christian philosophy and interviews with Balinese dalang, artisans, Christian writers, and Catholic priests. The study faced challenges in balancing theological reverence with cultural adaptation, which were addressed through contextual design exploration. The outcome is a new form of visual metaphor of Jesus and Mary in Balinese wayang style that reflects both spiritual depth and local aesthetic sensibility, offering a fresh model of religious visual acculturation.